An assessment of effectiveness of outsourcing services in quality service delivery in public sector : A case of Tanzania electric supply company limited, Tanga. - Mgweno, Zua (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University, Tanga Campus in partial fulfillment of the requirements for the award of the degree of Master of Business Adminstration in Corporate Management (MBA-CM) of Mzumbe University